Wahyu yang hilang, negeri yang guncang - Onghokham, 1933-2007. (Pusat Data dan Analisa Tempo, 2003)
Festschrift in honor of Onghokham, an Indonesian historian; articles previously published in Tempo magazine from 1976-2002.